An examination factors influencing the intention to adopt internet banking among SMES in Yemen: using an extension of the technology acceptance model (TAM) - Al-Fahim, Nabil Hussein; Wan Jusoh, Wan Jamaliah; Abideen, Adewale Abideen (JIBC Publisher, 2016)
Although the wide adoption of Internet banking service in developed countries, its application is still low in developing countries like Yemen. Moreover, there is a dearth of empirical research on Internet banking services in Yemen and this makes it necessary to carry out research on adoption of Internet banking service. The purpose of this study is to examine and investigate the main factors which influence the adoption of Internet banking services by Small and Medium Enterprise (SME) managers or owners in Yemen. The research framework consists of seven latent variables, four exogenous variables and three endogenous variables. Out of 920 SME managers or owners located in Sana’a (capital city), 311 respondents (35% response rate) were eventually used to analyze the data using Structural Equation Modeling (SEM) to examine causal and mediating relationship between the latent variables. The results of the study indicate that usefulness and ease of use are significant and positive effect towards Internet banking services adoption (IBSA). It also reveals that ICT readiness, financial institution support and competitive pressure are significant and positive effect towards usefulness and ease of use. It is found that usefulness, ease of use and regulatory support are significant towards (Internet Banking Services Adoption (IBSA). It can be concluded that TAM is found to be a good and suitable underpinning theory to explain IBSA factors in Yemen by achievement of model goodness of fit for the GOF index. The study also discussed implications for Yemeni contexts.